Synthesis of Uniform Polymer Encapsulated Organic Nanocrystals through Ouzo Nanocrystallization (Small Methods 1/2022). Issue 1 (18th January 2022) - Middha, Eshu; Chen, Chengjian; Manghnani, Purnima Naresh; Wang, Shaowei; Zhen, Shijie; Zhao, Zujin; Liu, Bin
Abstract : Ouzo Nanocrystallization In article number 2100808, Liu and co‐workers report the simple and novel approach of ouzo nanocrystallization for the synthesis of small and highly uniform organic nanocrystals with photoluminescent properties. The process of ouzo nanocrystallization helps in bringing the unique properties of organic dyes to real biomedical applications.